The support-based factors that facilitate work-family enrichment for working fathers in South Africa - Wallace, Chelsea Lee (Organisational Psychology, 2015)
Over the past two decades work-family researchers have increasingly explored the benefits of multiple role engagement. Work-family enrichment (WFE) is one construct reflecting the positive interaction between work and family. Yet there is a gap in our understanding of how fathers in South Africa experience WFE and how their organisations and their families can support them in managing their multiple role involvement in a way that enhances their performance in both domains. This study examined three sources of work based support (top management, supervisor and co-worker) and three sources of family-based support (spousal, extended family and paid domestic helpers) in relation to work-to-family and family-to-work enrichment. Working fathers in South African organisations responded to a self-report survey (N = 229). Exploratory factor analysis revealed that WFE is a unidimensional construct, contrary to expectations. Multiple regression analysis showed that co-worker and spousal support were statistically significant predictors of WFE. Baron and Kenny's (1986) approach was used to test the mediational effect of opportunities for professional development (OPD) on the relationship between work support (supervisor and co-worker) and WFE; however, OPD was not a significant mediator. Suggestions for future research are discussed in addition to theoretical and managerial implications associated with this study.